Biodiversity of Drosophila sp. from the Natural Environment based on the Cytochrome Oxidase subunit 1 Gene - M. Wurarah; Y. S. Mokosuli; H. M. Sumampouw (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Research on insect phylogenetics is intricated by their similar morphology and significant genetic diversity. The cytochrome oxidase subunit 1 (CO1) gene is the most widely utilized mitochondrial DNA gene in the identification and study of animal molecular biodiversity. This study aims to identify and reconstruct the phylogeny of fruit flies from North Sulawesi using the cytochrome oxidase subunit 1 (CO1) gene. Fruit flies were obtained from 5 (five) areas in North Sulawesi, namely Siau (L1), North Minahasa (L2), Minahasa (L3), Southeast Minahasa (L4), and Bolaang Mongondow (L5). Fruit fly imago limbs were used as a tissue source for genomic DNA extraction. Genomic DNA extraction was carried out using the Quick-DNAâ„¢ Miniprep Kit manufacture protocol. The CO1 gene amplification was carried out by the PCR method, and the visualization of the amplicons was carried out by the 1.5% gel electrophoresis method. Nucleotide sequencing used a sequencing service at First BASE Singapore with a bidirectional sequencing method. CO1 gene amplification of each sample was visualized at 690 bp to 702 bp length. After analyzing the CO1 gene concession area using the MEGA XI program, it is found that Drosophila at L1 has 702 bp, L2 has 703 bp, L3 has 698 bp, L4 has 700 bp, and L5 has 697 bp. Based on alignment analysis using the BLAST method, it is found that the L1 fruit fly has a similarity rate of 99.29% (E=0.0) to Drosophila parapallidosa [MK659836.1]. The L2 fruit fly also has a similarity rate of 96.86% with Drosophila parapallidosa [MK659836.1]. The L3 fruit fly has a similarity level of 94.94% with Drosophila parapallidosa [MK659836.1]. The L4 fruit fly has a similarity rate of 94.43% with Drosophila parapallidosa [MK659836.1]. However, the L5 fruit fly shows a similarity rate of 96.86% with Drosophila rubida [EU493593.1]. The reconstruction results with the MEGA XI program using the Minimum Evolution model obtain two monophyletic groups where the fruit fly in Bolaang Mongondow is in a monophyletic group different from other fruit flies. The results of this study prove the variation in fruit fly species in North Sulawesi based on the identification of the CO1 gene.